The Influence of Democratic Leadership on Employee Performance at The Department of Women's Empowerment, Child Protection and Community (DP3AM) Of Binjai City - Arif Pohan, Muhammad; Farida Ferine, Kiki (Proceedings of the International Conference on Multidisciplinary Science (INTISARI), 2024)
The aim of this research is to determine and analyze the influence of Democratic Leadership on Employee Performance in the Department of Women's Empowerment, Child Protection and Community Services in Binjai City. This research was carried out at the Department of Women's Empowerment, Child and Community Protection, Binjai City. The type of research is associative quantitative. The sample in this study was 61 employees of the Women's Empowerment, Child and Community Protection Department of Binjai City. The sampling technique in this research uses saturated samples so that the entire population will be a sample of 61 people. The research results show that Democratic Leadership has a significant influence on Employee Performance as shown by the T-Statistic value of 3,782 > 1.670 and the P Value of 0.003 < 0.05. The adjusted R Square value is 0.257 or 25.70%, which means that democratic leadership has a low influence on employee performance, while the remaining 74.30% is influenced by other factors that have not been studied. This shows that improvements in Democratic Leadership will be able to improve the performance of employees of the Women's Empowerment, Child Protection and Community Services of Binjai City.